Implementation of NLP-Based AI in German Wordle Game for the Provision of Automated Sentence Examples - Aminmahrup, Ridwan Setiawan; Muhammad Iqbal (Cattleya Darmaya Fortuna, 2026)
This study implements an artificial intelligence system based on Natural Language Processing (NLP) in a German-language Wordle game with the aim of providing automatically generated example sentences for each appearing word. The system is designed not only to display the correct answer, but also to present contextual usage of the word through simple and easily understandable sentences. The development process involves German text analysis, including verb tense forms (Zeitformen), verb conjugation, word structure, and basic sentence patterns, supported by Natural Language Processing techniques to generate example sentences and German– Indonesian translations automatically. Therefore, this system is expected to assist users in learning the German language through word- based game activities.